THE RELATIONSHIP BETWEEN HIGH BORROWING AND LOW AVAILABILITY OF QUALITY GOVERNMENT SERVICES IN KUWAIT - Hanan Alhajeri, (PEOPLE: International Journal of Social Sciences, 2025)
Kuwait is famous for its oil reserves, which make it one of the richest countries in the world. However, its public services, including healthcare, housing, education, and infrastructure, lack quality. This has led to citizens borrowing heavily to compensate for the deficiency in public services. This research paper aims to study the relationship between high borrowing among citizens and the low quality of public services, focusing on healthcare, the lack of street maintenance, the low level of education, the shortage of recreational cities, and the failure to provide adequate housing care. Methodology: This study used a mixed method approach, including both quantitative and qualitative methods. The study relies on secondary data from the Central Bank of Kuwait, the Ministry of Health, the Ministry of Education, and the Ministry of Public Works to obtain information on citizens' borrowing behavior and the quality of public services. The study also relies on a public opinion survey of citizen borrowers to obtain their views on the impact of low-quality public services on their borrowing behavior. Results: The results of the data analysis showed that the study population is not satisfied with the public services provided by the state, and that citizens' motives for borrowing are related to obtaining better housing services and spending on private health and education services.